Location Quality Analysis (LQ) in Determining Basic and Non-Basic Sectors in Berau Regency - Puspitasari, Lisa; Bayu, Muhammad; Almani, Almani (Universitas Gorontalo, 2025)
The basic sector is a sector that plays a role as the primary mover of the economy in the growth of a region and is also competitive in the market, thereby increasing exports from that region. The non-basic sector only serves to meet local demand. The purpose of this study is to identify the basic and non-basic sectors in Berau Regency. This study uses secondary data obtained from the Central Statistics Agency (BPS) for the period 2016-2022 with the Location Quotient (LQ) analysis tool. The results of the study show that there are eight basic sectors, including mining and quarrying, real estate, education services, health and social services, transportation and warehousing, government administration, defense and social security, agriculture, forestry and fisheries, and other services, which are also basic sectors in Berau Regency because they have an LQ value greater than 1. These basic sectors are able to meet the needs of the market in Berau Regency as well as markets outside Berau Regency. It also states that there are nine non-basic sectors, including the electricity and gas supply sector, the manufacturing sector, the water supply sector, waste management, waste and recycling, the construction sector, the wholesale and retail trade sector, the accommodation and food and beverage sector, the information and communication sector, the financial and insurance services sector, and the corporate services sector, as they have an LQ value of less than 1. These non-basic sectors are only capable of meeting the needs of the region itself